From the History of Forming and Developing the Concept of the National Innovative System - Qoqiauri, Lamara (Asian Development Policy Review, 2017)
The field of my scientific studies during last period have included extremely active field – innovations and the problems related with them. The Article touches upon historic issues of formation of the effective national innovation system. Particularly, the factors determining the concept of national innovation system are represented, together with the main stages of its evolution. We tried to represent the image of scientific study of origination, formation and development of the concept in logical order; the role of the researchers, who are famous worldwide and scientific merit in the establishment of the theory of the concept of national innovation system.